Winning the mixed team event at major international archery competitions - Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
Major international target archery competitions usually include a 72-arrow ranking round, followed by one-on-one knockout matches conducted over a small number of arrows, until one archer or team remains. This article considers the mixed pair team event that includes teams consisting of one male and one female archer, both using the same bow type. The relation between a team`s place in the ranking round and the likelihood of that team finishing in a top position following the one-on-one knockout matches has been modelled and compared to the results from competitions from 2010 to 2017 inclusive. The team`s ranking round score has been used to indicate the ability of each archer in the matches and to calculate the probability of the team winning sufficient matches in succession to succeed in the competition. The study found that the probability of the team winning the competition decreases exponentially with ranking place. Due to the importance of the ranking round, a team must finish in or near the top seven places in the ranking round for the team to have a reasonable chance at winning a medal.